DAMPAK BUDAYA K-POP TERHADAP GAYA KOMUNIKASI REMAJA INDONESIA DI JAKARTA: STUDI KASUS PARA PENGGEMAR GEN Z - Amalia Kartika; Mareta Puri Rahastine (Jurnal Riset Multidisiplin Edukasi, 2025)
The popular culture of South Korea, widely known as K-Pop, has become a global phenomenon with a significant influence across various countries, including Indonesia. This study aims to analyze and understand the impact of K-Pop culture on the communication styles of Indonesian adolescents in Jakarta, particularly those categorized as Generation Z. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews with active K-Pop fans, participatory observation, and documentation from social media and fan communities. The results indicate that K-Pop culture influences the communication style of teenagers in several aspects, including the use of Korean phrases and fandom-specific terms in daily conversations, changes in nonverbal communication styles such as expressions and body gestures, and increased digital interaction through social media. K-Pop culture also shapes social and group identity among teenagers, where they adapt their communication patterns based on the norms of the fan culture they are involved in. On the positive side, this cultural influence encourages youth to be more open to global cultures, enhances their interest in learning foreign languages, and broadens their social networks in the digital space. In conclusion, K-Pop culture has brought complex influences on the communication styles of Generation Z in Jakarta. These influences are not only linguistic but also social, cultural, and psychological. Therefore, it is important for parents, educators, and policymakers to understand this dynamic in order to provide appropriate guidance in responding to the presence of global cultural trends.